Constituintes de Senecio platensis Arech. isolamento, elucidação estrutural e avaliação da atividade antibacteriana - Bolzan, Aline Abati (2007)
The genus Senecio (Asteraceae) constitutes a group of cosmopolitan plants formed by more than 2000 species. Although most of these plants are considered to be toxic due to the presence of pyrrolizidine alkaloids, several of them are used in folk medicine. Their medicinal use can be attributed to other secondary metabolites, amongst them the terpenoids, with known antimicrobial activity. This work describes the isolation and identification of three compounds present in the CH2Cl2 extract of fresh aerial parts of Senecio platensis Arech., a species that showed the presence of peroxides in a phytochemical screening. Additionally, the the antibacterial activity of the isolated secondary metabolites has been evaluated. The aerial parts of Senecio platensis were collected in Capão Novo RS, Brasil and identified by Prof. Dr. Nelson Ivo Matzenbacher. Voucher specimen SMDB 9522 is preserved in the Herbarium of the Departamento de Botânica, UFSM. The fresh aerial parts of S. platensis (350.0 g) were extracted by maceration with CH2Cl2. The CH2Cl2 extract was evaporated to obtain an viscous residue (6.0 g), which approximates a yield of 1.71%. The crude extract was fractionated by flash chromatography over silica gel, using CH2Cl2 and CH2Cl2:EtOH mixtures of increasing polarity to yield 29 fractions. After two cycles of column chromatography (column: silica gel impregnated with AgNO3 (10%), eluents: hexane:acetone (95:5) and hexane:ethyl ether (99:1) 13.3 mg of PP1 were isolated from fraction 1 and later identified as germacrene D. After successive column chromatography over silica gel impregnated with AgNO3 (10%), eluting with hexane:acetone (9:1), hexane:ethyl acetate (95:5) and hexane:acetone (93:7), fraction 5 yielded 17.0 mg of AB1 (dehydrofukinone) and 30.6 mg of AB2 (spathulenol). The compounds were analyzed by GC-EI-MS, 1H and 13C NMR and were identified by comparison of their spectroscopic data with the literature. The fraction containing germacrene D, which is considered to be a precursor of several other sesquiterpene derivatives, was submitted to photooxidation process using Bengal Rose as sensitizer agent. By this reaction it was possible to confirm the formation of germacrene-D-1-hydroperoxide by its precursor. The antibacterial evaluation of the isolated compounds was accomplished by the broth microdilution method based on M7-A6/CLSI. In relation to Bacillus cereus ATCC 14579, dehydrofukinone showed MIC of 256 μg/mL and MBC of 4096 μg/mL. The spathulenol presented MIC and MBC of 64 μg/mL. Against the clinical isolate of B. cereus, dehydrofukinone showed MIC of 256 μg/mL and MBC > 8192 μg/mL while spathulenol showed MIC 32 μg/mL and MBC > 8192 μg/mL. Dehydrofukinone and spathulenol are inactive against Pseudomonas aeruginosa at the tested concentrations (until 8192 μg/mL).